Effects of ultrasound and high pressure on physicochemical properties and HMF formation in Turkish honey types. (February 2018) - Önür, İpek and Misra, N.N. and Barba, Francisco J. and Putnik, Predrag and Lorenzo, Jose M. and Gökmen, Vural and Alpas, Hami
Abstract: In industrial production, thermal processing of honey at 50 °C commonly induces liquefaction, i.e. it reduces the crystal count and viscosity and delays any subsequent crystallization. Unfortunately, thermal treatment can generate toxic 5-hydroxymethylfurfural (HMF), thereby resulting in quality reduction. Considering this, the present work aims at evaluating the influence of (two) processing technologies as alternatives to thermal processing of honey, namely high hydrostatic pressure (HHP; P = 220–330 MPa, T = 50/60 °C, t = 23/106 min), and ultrasound processing (US; at 24 kHz). The quality parameters evaluated for honey included liquefaction time, HMF content, diastase number, colour and viscosity. The best process conditions for maximising liquefaction were found to be P = 220 MPa, T = 50 °C, t = 106 min for HHP, and a 7 mm probe with 0.5 cycles (batch) for US treatment. US treatment is recommended over thermal processing owing to the convenience, shorter processing times, and less quality loss. Likewise, HHP treatment was shorter and with lower HMF values than thermal processing. In conclusion, ultrasound and HHP are both potential alternatives to thermal processing for liquefaction of honey crystals. Highlights: Thermal, Ultrasound (US) and HHP processing evaluated for liquefaction of honey. Ultrasound found to promote rapid dissolution of crystals. Liquefaction times were shorter with thermal assisted HHP. Relatively lower HMF formation observed with HHP treatments.